A latent class analysis of factors influencing preferences for infant respiratory syncytial virus (RSV) preventives among pregnant people in the United States - Martine C. Maculaitis; Brett Hauber; Kathleen M. Beusterien; Oliver Will; Lewis Kopenhafer; Amy W. Law; Jeffrey T. Vietri; Joseph C. Cappelleri; Joshua R. Coulter; Sarah Pugh; Kimberly M. Shea (Taylor & Francis Group, 2024)
A maternal vaccine and long-acting monoclonal antibody (mAb) were recently approved to protect infants against respiratory syncytial virus (RSV). We identified subgroups of pregnant people with different preferences for RSV preventives and respondent characteristics associated with subgroup membership. An online survey, including a discrete choice experiment (DCE), was conducted among US pregnant people. RSV preventive attributes included effectiveness, duration of protection during RSV season, injection recipient/timing, preventive type (vaccine or mAb), and type of visit required to receive injection. In DCE choice tasks, pregnant people selected between two hypothetical preventive profiles with varying attribute-levels and a no-preventive option. Logistic regression, including latent class analysis (LCA), was used to analyze the data. Of 992 pregnant people (mean age: 30.0 years), 60.3% were expecting their second/later birth. LCA identified three preference subgroups: 'Effectiveness' (preventive choice mostly driven by increases in effectiveness; 51.4% class membership probability), 'Season' (preventive choice mostly driven by improvement in duration of protection during the RSV season; 39.2% class membership probability), and 'No Preventive' (frequently chose no-preventive option; 9.4% class membership probability). 'Effectiveness' and 'Season' preferred maternal vaccine over mAb; mAb was preferred by 'No Preventive.' Perceiving RSV as serious for infants, higher health literacy, and lower household income were associated with 'Effectiveness.' Perceiving RSV as serious for pregnant people was associated with 'Season.' Perceiving RSV to not be serious for pregnant people and not being employed were associated with 'No Preventive.' Subgroups of pregnant people vary in preferences for RSV preventives. Most pregnant people preferred a maternal vaccine, although some may be more willing to accept alternative preventive options.